Penerapan Model Pembelajaran Problem Based Learning (PBl) untuk Meningkatkan Motivasi Belajar Pendidikan Agama Islam dan Budi Pekerti Siswa Kelas XI SMK Assalaam Bandung - Kamil Amarudin Solihin; Nurul Afrianti (Bandung Conference Series: Islamic Education, 2024)
Abstract. Kamil Amarudin Solihin. 10030120168. Application of the Problem Based Learning (PBL) Learning Model to To Increase Motivation for Learning Islamic Religious Education and Character of Class XI Students at Assalaam Vocational School Bandung. The learning model is the design of learning activities to ensure learning is effective. This research aims to: 1) analyze the objective conditions of PAIBP learning motivation for class XI students at Vocational School Assalaam Bandung before using the PBL learning model; 2) analyze the application of the PBL learning model in increasing the motivation of class XI students in PAIBP learning at SMK Assalaam Bandung; 3) analyze the influence of the PBL learning model in increasing the learning motivation of class XI students in PAIBP learning after using the PBL learning model at SMK Assalaam Bandung. This research uses a quantitative approach experimental method. This research shows that students' learning motivation decreased before implementing the PBL model, but increased after. The average score for student learning motivation in the experimental class (84.49) was higher than the control class (70.37), indicating that the application of the PBL model increased students' learning motivation in PAIBP subjects. This can be seen from the results of the Paired-Samples t-Test which obtained a Sig (2-tailed) = 0.000. Based on the tests that have been carried out, it can be said that is rejected and is accepted because 0.000 < 0.05. Thus, it can be concluded that there is a significant influence on the use of the PBL learning model on increasing the learning motivation of class XI TKR students in PAIBP subjects at SMK Assalaam Bandung. Abstrak. Kamil Amarudin Solihin. 10030120168. Penerapan Model Pembelajaran Problem Based Learning (PBL) Untuk Meningkatkan Motivasi Belajar Pendidikan Agama Islam Dan Budi Pekerti Siswa Kelas XI SMK Assalaam Bandung. Model pembelajaran merupakan perancangan kegiatan belajar untuk memastikan pembelajaran berjalan efektif. Penelitian ini bertujuan untuk: 1) menganalisa kondisi objektif motivasi belajar PAIBP siswa kelas XI di SMK Assalaam Bandung sebelum menggunakan model pembelajaran PBL; 2) menganalisa penerapan model pembelajaran PBL dalam meningkatkan motivasi siswa kelas XI dalam pembelajaran PAIBP di SMK Assalaam Bandung; 3) menganalisa pengaruh model pembelajaran PBL dalam meningkatkan motivasi belajar siswa kelas XI dalam pembelajaran PAIBP sesudah menggunakan model pembelajaran PBL di SMK Assalaam Bandung. Penelitian ini menggunakan metode eksperimen pendekatan kuantitatif. Penelitian ini menunjukkan bahwa motivasi belajar siswa menurun sebelum menerapkan model PBL, tetapi meningkat setelahnya. Perolehan nilai rata-rata motivasi belajar siswa di kelas eksperimen (84,49) lebih tinggi daripada kelas kontrol (70,37), menunjukkan bahwa penerapan model PBL meningkatkan motivasi belajar siswa pada mata pelajaran PAIBP. Hal ini dapat dilihat dari hasil uji Paired-Samples t-Test yang memperoleh nilai Sig (2-tailed) = 0.000. Berdasarkan pengujian yang sudah dilakukan, maka dapat dikatakan bahwa ditolak dan diterima karena 0.000 < 0.05. Dengan demikian, dapat disimpulkan bahwa terdapat pengaruh yang signifikan pada penggunaan model pembelajaran PBL terhadap peningkatan motivasi belajar siswa kelas XI TKR pada mata pelajaran PAIBP di SMK Assalaam Bandung.